2011
DOI: 10.1593/neo.111060
|View full text |Cite
|
Sign up to set email alerts
|

Merlin-Deficient Human Tumors Show Loss of Contact Inhibition and Activation of Wnt/β-Catenin Signaling Linked to the PDGFR/Src and Rac/PAK Pathways

Abstract: Neurofibromatosis type 2 (NF2) is an inherited predisposition cancer syndrome characterized by the development of multiple benign tumors in the nervous system including schwannomas, meningiomas, and ependymomas. Using a disease model comprising primary human schwannoma cells, we previously demonstrated that adherens junctions (AJs) are impaired in schwannoma cells because of a ubiquitous, upregulated Rac activity. However, the mechanism by which loss of contact inhibition leads to proliferation remains obscure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 41 publications
5
65
1
Order By: Relevance
“…Positive regulation of canonical Wnt signaling by Pak2 has been reported also (31). Although contrary to our findings, this result perhaps is not surprising, given that Rac1 acts positively in canonical Wnt signaling (32) and functions in both canonical and noncanonical Wnt signaling (Fig.…”
Section: Pak1 Negatively Regulates Canonical Wnt Signaling In Hek293tcontrasting
confidence: 99%
“…Positive regulation of canonical Wnt signaling by Pak2 has been reported also (31). Although contrary to our findings, this result perhaps is not surprising, given that Rac1 acts positively in canonical Wnt signaling (32) and functions in both canonical and noncanonical Wnt signaling (Fig.…”
Section: Pak1 Negatively Regulates Canonical Wnt Signaling In Hek293tcontrasting
confidence: 99%
“…Our suggestion of Tiam1 as a critical component of tumorigenesis is consistent with recent reports that attribute the connection of Tiam1/Rac and c-Myc to the Wnt pathway. [52][53][54] For example, in colorectal cancer cells, a complex of Tiam1, Rac1, and the key Wnt-mediator b-catenin binds to the Wnt-responsive promoters of c-Myc and cyclin D1, thereby enhancing their transcription. 53 Furthermore, Rac1 is involved in regulating the phosphorylation of the signal transducer and activator of transcription 3, which results in the transcriptional induction of c-Myc.…”
Section: Discussionmentioning
confidence: 99%
“…20 The other study showed that activated Src phosphorylates Tyr654 in β-catenin, which promotes dissociation of the membrane portion of β-catenin, resulting in accumulation of active β-catenin in nuclei of Merlin-deficient human schwannoma cells. 21 In this report, we provide a novel mechanism for the inhibition of Wnt/β-catenin signaling by Merlin. Merlin interacts with and inhibits phosphorylation of LRP6 by blocking the interaction between Axin and LRP6.…”
mentioning
confidence: 95%